Tradução, adaptação transcultural e validação da versão brasileira do Impact of fixed appliances measure (B-IFAM) - Ana Paula Sales Rebouças (2016)
Introduction: The aim of this study was translate and cross-culturally adapt the condition-specific instrument Impact of Fixed Appliances Measure (IFAM), to Brazilian Portuguese , assessing its validity and reliability for use among Brazilian children/adolescents. Methods: The instrument was translated from English to Portuguese independently by two bilingual translators. Then, the two translated versions were submitted to the committee review, resulting in a single version, which was back-translated by another bilingual translator. This first version of the instrument in Portuguese was pretested on a sample of 15 children/adolescents, resulting in the Brazilian version of IFAM (B-IFAM). The B-IFAM was tested on 161 children/adolescents, between 10 to 18 year old, who were undergoing orthodontic treatment at the Orthodontic Clinic, School of Dentistry, Federal University of Minas Gerais. Internal consistency was assessed using Cronbachs alpha () and test-retest reliability by intraclass correlation coefficients (ICC). The construct validity and convergent validity were assessed by Pearsons correlation. Convergent validity was conducted among the B-IFAM and the Brazilian version of Child Oral Impact on Daily Performance (Child-OIDP). Discriminant validity was evaluated by comparisons of B-IFAMs means and SD with gender and children's/adolescents Angles classification using Students t-test. Results: Internal consistency was 0.89 for overall score and 0.55 to 0.86 for subscales. ICC for test-retest reliability for B-IFAMs overall score was 0.81 and for subscales, ranged from 0.55 to 0.78. Pearsons correlation between overall score of B-IFAM and Child-OIDP was r=0.28 (p<0.01). The B-IFAM demonstrated acceptable construct validity, which most correlations presenting p<0.05. Discriminant validity demonstrated statistically significant difference between children/adolescents classified as Class I and Class II/III malocclusion in Aesthetic and Functional Limitation subscales (p <0.05). Conclusions: The B-IFAM demonstrated adequate psychometric properties regarding reliability and validity. The study achieved a specific-condition instrument feasible to measure the impact of orthodontic treatment on quality of life of Brazilians children/adolescents.